Chinese college students collaborative mobile-assisted language learning experience and flow as a key factor for further adoption - Hu, Ling; Hei, Dan; Wang, Hui; Dai, Xuanrui (Frontiers in Psychology, 2023)
In recent years, the widespread shift towards online learning in higher education has led to a notable increase in the utilization of collaborative mobile-assisted language learning (MALL). However, the efficacy and implementation of MALL in college settings remain subjects of ongoing scholarly debate. To gain deeper insights into the experiences of Chinese college students with collaborative MALL and investigate factors that may influence their intentions for further adoption, this study proposed a comprehensive model that integrates the updated Unified Theory of Acceptance and Use of Technology (UTAUT) and flow theory. The model aimed to assess the relationship between flow and various antecedents, including perceived cost, social influences, perceived mobility, collaboration, and knowledge sharing, which shape students' intentions to adopt collaborative MALL. A survey was conducted among a sample of 831 students from 32 provinces and autonomous regions. The data analysis revealed that while 73% of participants reported having experienced collaborative MALL, overall adoption levels among Chinese college students are still in its initiative stage of adoption. Furthermore, variations were observed in the experiences of students from different majors and level of education. Importantly, the assessment of the proposed Mobile Collaborative Language Learning (MCLL) Model demonstrated the significant role of flow in predicting the adoption of collaborative MALL among Chinese college students. The study concludes with suggestions for future research opportunities based on the research findings, aiming to enhance our understanding and application of collaborative MALL in higher education contexts.